2013
DOI: 10.4049/jimmunol.1202144
|View full text |Cite
|
Sign up to set email alerts
|

Flagellin Induces Myeloid-Derived Suppressor Cells: Implications for Pseudomonas aeruginosa Infection in Cystic Fibrosis Lung Disease

Abstract: Pseudomonas aeruginosa persists in patients with cystic fibrosis (CF) and drives CF lung disease progression. P. aeruginosa potently activates the innate immune system, mainly mediated through pathogen-associated molecular patterns, such as flagellin. However, the host is unable to eradicate this flagellated bacterium efficiently. The underlying immunological mechanisms are incompletely understood. Myeloid-derived suppressor cells (MDSCs) are innate immune cells generated in cancer and proinflammatory microenv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(137 citation statements)
references
References 52 publications
7
128
1
1
Order By: Relevance
“…When viewed in combination, these markers were suggestive of a granulocytic/neutrophilic MDSC subtype (PMN-MDSCs). 18,29 Percentages of monocytic MDSCs in peripheral blood were substantially lower (monocytic MDSCs mean 0.12% before ECP) compared with PMN-MDSCs (mean 6% before ECP) in our patient cohorts and did not change significantly upon ECP treatment (Supplementary Figure 2). We therefore systematically followed up on the observation that ECP Table 1.…”
Section: Ecp Rapidly Increases Neutrophilic Mdscs In Gvhd Patientsmentioning
confidence: 94%
“…When viewed in combination, these markers were suggestive of a granulocytic/neutrophilic MDSC subtype (PMN-MDSCs). 18,29 Percentages of monocytic MDSCs in peripheral blood were substantially lower (monocytic MDSCs mean 0.12% before ECP) compared with PMN-MDSCs (mean 6% before ECP) in our patient cohorts and did not change significantly upon ECP treatment (Supplementary Figure 2). We therefore systematically followed up on the observation that ECP Table 1.…”
Section: Ecp Rapidly Increases Neutrophilic Mdscs In Gvhd Patientsmentioning
confidence: 94%
“…Recently, Zhao et al (37) showed an association of an upregulation of CXCL12 and an accumulation of MDSCs in the pregnant mouse uterus. Moreover, GR-MDSCs in CF patients were recently shown to express CXCR4 (16). Because AMD3100 only partially blocked suppressive activity, other mechanisms besides CXCR4 may be involved in MDSC activation.…”
Section: Discussionmentioning
confidence: 99%
“…1A). plaGR-MDSCs showed the typical morphology of granulocytic cells with a segmented nucleus (12,14,16,22) (Fig. 1B).…”
Section: Gr-mdscs Accumulate At the Maternal-fetal Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…These findings demonstrate that MDSCs can suppress Th17 response. In another study, MDSCs derived from patients infected with Pseudomonas aeruginosa evidently dampened the IL-17 protein production by CD4 + T cells and suppressed IL-17 protein expression in T cells (99). A previous T cell study demonstrated that the circulating percentages of neutrophilic MDSCs in graft over that in host disease patients treated with extracorporeal photopheresis increased rapidly (100).…”
Section: Mdscs and Th17 Cellsmentioning
confidence: 99%